دور المجتمع المدني في الإصلاح السياسي في الجزائر (1962-2016) - العلمي, يعقوب (جامعة الوادي university el-oued)
من خلال هذه الدراسة التي يبين مدى فاعلية مؤسسات المجتمع المدني في تفعيل الإصلاح السياسي في الجزائر وذلك بدراسة كل دستور وما جاء به من إضافة لتعزيز فاعلية المجتمع المدني في كل مرحلة من مراحل الحكم بدءا بدستور 1963 مرورا بكل التعديلات التي تلته والدساتير التي جاءت من بعده إلى غاية تعديل 2016باعتباره آخر تعديل ، كما عرجنا بالحديث على واقع المجتمع المدني من خلال دراسة نشاطاته وأفعاله ومساهمته في المحافظة على مؤسسات الدولة من خلال تنشئة المواطن وتثقيفه سياسيا بما يؤدي إلى وعيه الذي ينجم عنه المحافظة على نظام الحكم أو التغيير بطرق سلمية . " Through this study which shows effectiveness institutions of civil society in activating political reform in Algeria by studying every constitution it has com to add to enhance the effectiveness of civil society at each stage of the government . beginning with the 1963 constitution he went through all the amendments that followed and the constitutions that came after him until the amendment of 2016 as the last modification we also talked about the reality of civil society through the study of its activities and actions and its contribution to the preservation of state institutions by educating the citizen and educating him politically thereby leading to awareness of the maintenance of a system of government or change in peaceful and legitimate ways "
م.س.ع.19
Keywords: "الجزائر – المجتمع المدني –الإصلاح السياسي – الدساتير – الفاعلية –الواقع "; " Through this study which shows effectiveness institutions of civil society in activating political reform in Algeria by studying every constitution it has com to add to enhance the effectiveness of civil society at each stage of the government . beginning with the 1963 constitution he went through all the amendments that followed and the constitutions that came after him until the amendment of 2016 as the last modification we also talked about the reality of civil society through the study of its activities and actions and its contribution to the preservation of state institutions by educating the citizen and educating him politically thereby leading to awareness of the maintenance of a system of government or change in peaceful and legitimate ways "